2022
DOI: 10.1111/iep.12459
|View full text |Cite
|
Sign up to set email alerts
|

KLF13 overexpression protects sepsis‐induced myocardial injury and LPS‐induced inflammation and apoptosis

Abstract: Sepsis remains a worldwide public health problem. This study aims to explore the role and mechanism of transcriptional factors (TFs) in sepsis-induced myocardial injury. Firstly, TF KLF13 was selected to explore its role in sepsis-induced myocardial injury. The caecal ligation and puncture (CLP) -induced sepsis mouse model was established and the septic mice were examined using standard histopathological methods. KLF13 expression was detected in the septic mouse heart and was also seen in a lipoploysaccharide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Our findings are consistent with previous results that excessive cardiomyocyte apoptosis is tightly related to cardiac dysfunction in the CLP-induced sepsis model. 35 , 36 In addition, one study showed that IL-15 protected hypoxia-induced cardiomyocyte death through activation of STAT3 and PI3K-ERK1/2 pathways, 13 which maybe other possible mechanisms that contribute to the cardioprotective effect of IL-15. Finally, Inoue et al .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with previous results that excessive cardiomyocyte apoptosis is tightly related to cardiac dysfunction in the CLP-induced sepsis model. 35 , 36 In addition, one study showed that IL-15 protected hypoxia-induced cardiomyocyte death through activation of STAT3 and PI3K-ERK1/2 pathways, 13 which maybe other possible mechanisms that contribute to the cardioprotective effect of IL-15. Finally, Inoue et al .…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant enzymes, including SOD, SOD2, and peroxidases such as GPX and CAT, play a crucial role in antioxidant defense by regulating ROS levels [ 33 , 34 ]. A high concentration of LPS leads to abnormal ROS and MMP levels; promotes the production of inflammatory factors such as TNF-α, IL-1β, IL-6, and IL-8, causing oxidative damage and mitochondrial dysfunction [ 2 , 35 ]; and even leads to apoptosis [ 36 , 37 ]. Cecropin A has been shown to inhibit the production of TNF-α and IL-1β induced by LPS in mouse macrophage-derived RAW264.7 cells [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…As an antipyretic agent, XJDHT exhibits potent anti-inflammation effects and can decrease the expression of adhesion molecules by vascular endothelial cells. 23 , 33 , 34 Previous study demonstrated that XJDHT reduces the release of inflammatory cytokines such as IL-6 and improves survival in rats with sepsis via regulation of the HIF-1α signaling pathway. 18 Recent studies have reported that XJDHT suppresses aerobic glycolysis by down-regulating the TLR4/HIF-1α/PKM2 signaling pathway, therebyimproving prognosis in sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence suggests that most patients with septic shock suffer from myocardial depression. 19 The mechanisms underlying myocardial depression during sepsis predominantly include mitochondrial dysfunction, 20,21 cell death (necrosis and apoptosis), 22,23 and inflammation. 24,25 LPS is highly pathogenic and can induce severe sepsis, [26][27][28][29] accordingly, LPS is often used to induce myocardial injury in animal models.…”
Section: Discussionmentioning
confidence: 99%